Nilai-Nilai Filosofis dalam Kaba Rambun Pamenan Karya Sutan Mangkudun dkk - Ifnaldi Ifnaldi (Institut Agama Islam Negeri Curup, 2020)
Kaba (story) is an old literature of Minangkabau that brings with it local culture and languages. Such local languages need to be revitalized to sustain Indonesian culture and language. This study aimed to reveal the philosophical values contained in the Kaba Rambun Pamenan, the old Minangkabau literature. This study was solely carried out resting upon empirical facts or phenomena existing in the Kaba Rambun Pamenan by Sutan Mangkudun and Ilyas Sutan Mangkudun (1988). The data sources were recordings from an art performance at Taman Budaya Padang in 2010, the book of Kaba Rambun Pamenan by Sutan Mangkudun and Ilyas Sutan Mangkudun, and the Book of Cultural Values in Kaba Rambun Pamenan by Abdul Rahman. The data analysis techniques used inductive and deductive approaches. First, the researcher listened to and opened the video recording of the kaba rambun pamenan performance; second, he made a synopsis of the story; and third, he searched for the content of philosophical values in the kaba, and it was then narrated in the form of quotations in sentences. After the data were collected, further analysis based on the existing theory was conducted. The findings of the present study covered: (1) being a leader must be a wise leader; (2) being a child must be responsible for the family; (3) being a man must be brave and honest, polite, not arrogant, and humble; and (4) if going abroad, one must be honest and helpful